2020
DOI: 10.1097/nrl.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Deep Brain Stimulation on the Sexual Function of Patients With Parkinson’s Disease

Abstract: Background: Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is used in the treatment of advanced Parkinson’s disease (PD) with well-established benefits over motor complications. However, few studies addressing the impact of DBS on nonmotor dimensions such as sexual function have been conducted. This study aims to determine the effect of DBS-STN on the sexual activity of patients with PD and to establish predictive factors for sexual function decline after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
14
0
3
Order By: Relevance
“…Although the results of both instruments showed a moderate correlation between them and with depression, self-esteem, and CRQ, the SQ-F was correlated with a larger number of factors than FSFI, including cognition and severity of NMS. Furthermore, the results from multiple regression models confirmed that FSFI and SQ-F scores could be predicted by different factors: while depression severity was the unique able to predict the FSFI, the global cognitive capacity and that CRQ were the best predictors for the SQ-F. Based on this evidence, although most previous studies investigating SH in WwPD had used FSFI [12,16,20,27,30,36,43], the addition of an evaluation over a longer term by SQ-F may offer a more comprehensive disease impact on SH..…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although the results of both instruments showed a moderate correlation between them and with depression, self-esteem, and CRQ, the SQ-F was correlated with a larger number of factors than FSFI, including cognition and severity of NMS. Furthermore, the results from multiple regression models confirmed that FSFI and SQ-F scores could be predicted by different factors: while depression severity was the unique able to predict the FSFI, the global cognitive capacity and that CRQ were the best predictors for the SQ-F. Based on this evidence, although most previous studies investigating SH in WwPD had used FSFI [12,16,20,27,30,36,43], the addition of an evaluation over a longer term by SQ-F may offer a more comprehensive disease impact on SH..…”
Section: Discussionmentioning
confidence: 56%
“…In the absence of any illness, the aging process plays a key role in the development of SD [11]. Age is an independent predictive factor for developing erectile dysfunction in men and SD in women [12]. However, the aging effect on SH in PD is a complex issue and several studies showed that SD and sexual satisfaction in PD worsened with aging [13,14,15,16].…”
mentioning
confidence: 99%
“…Our multiple regression models revealed that different factors predicted scores on each instrument, with quality of marital relationship predicting general short-term SH (IIFE total score), motor disability predicting EF domain, and depression predicting SQ-M. Although the majority previous studies have used IIEF, primarily EF domain, [11,14,20,36,39] to evaluate SF in MwPD, our findings suggest that incorporating the SQ-M questionnaire can provide additional insight into how the PD affects SH.…”
Section: Discussionmentioning
confidence: 93%
“…The ranges of scores allow classifying erectile dysfunction (ED) into five categories, based on the domain of erectile function, with scores ranging from 6 to 30: without ED (26-30); mild ED (22)(23)(24)(25); mild to moderate ED (17)(18)(19)(20)(21); moderate ED (11)(12)(13)(14)(15)(16); severe ED (6)(7)(8)(9)(10).…”
Section: International Index Of Erectile Function (Iief) -Short-term Shmentioning
confidence: 99%
“…DBS-STN has no direct effect on the PD patients’ sexual life. Emotional well-being may contribute to a different opinion of the sexual function according to the patient’s sex [ 32 ].…”
Section: Discussionmentioning
confidence: 99%